Analisis Dampak Kelangkaan Minyak Goreng Terhadap Umkm Kuliner di Kota Samarinda - Sutrisno, Sutrisno; Arwin, Arwin; Hamka, Rezky Amalia; Pratama, Muhammad Isbar (Peneliti.net, 2023)
Polemics occur in the community because the availability of cooking oil is very scarce, of course this is in contradiction with the volume of production of palm oil as a raw material for cooking oil which is actually very adequate. The increase in the price of cooking oil had an effect on the high cost of production for MSME products. With an increase in production costs, MSME actors must also increase the selling price of their products so that it will affect the process of market demand and supply. The purpose of this study was to determine the impact of the scarcity of cooking oil on Culinary MSME Income in the city of Samarinda. The research method used in this research is exploratory descriptive qualitative with a case study approach. The data collection techniques used were interviews, questionnaires and observations of MSME actors. The data analysis technique used is Miles & Huberman theory which consists of data reduction, data presentation and conclusion. The results showed that the scarcity and increase in cooking oil caused an increase in production costs by 40% and income decreased by around 33%-53%. The conclusion from this study is that the increase in cooking oil has had a huge impact on culinary MSMEs in Samarinda City.